Architectural Archives: The Jean-Jacques Deluz Collection (1930–2009) and the Construction of a Body of Research on Post-colonial Algiers - Mourad Bouzar (Journal of Open Humanities Data)
In Algeria, where the dispersed nature of sources from the colonial period is compounded by the difficulties of accessing archives and areas of research in the post-independence period, architects’ archives are an essential resource. Studying them broadens our understanding of the evolution of cities and buildings, and exploring the ideas and influences that have shaped their development. This article is based on a PhD thesis entitled Jean-Jacques Deluz (1930–2009): itinéraire d’un architecte suisse à Alger. Du tout au fragment (Bouzar, 2022). It focuses on the journey of an architect between Switzerland, Algeria and France, and was largely based on his personal archives deposited in 2014 at the Algiers Diocesan Study Center, known as the “Glycines”. Deluz was a key contributor to the urban and architectural history of Algiers in the twentieth-century. He remained in Algeria after Independence and turned, from 1962 onwards, to becoming an independent architect, a professional status he never abandoned. In addition to highlighting certain major segments of the Deluz collection, this research paper discusses the notion of corpus in the light of the objectives of monographic art-historical research into the filiations of Deluz’s work. Through an analysis of a body of research on an architect, this paper proposes avenues of research for the study of urban, economic and social policies in post-colonial Algiers.